2021
DOI: 10.1002/lno.11927
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic and biological controls of biofilm nitrogen uptake in gravel‐bed streams

Abstract: Epibenthic biofilms are important in regulating nitrogen (N) fluxes in stream ecosystems. The efficiency of the regulation is controlled by hydraulic and biological processes and their interactions. However, knowledge on the underlying physical and biological processes, their controlling parameters, and interactions in stream ecosystems is still limited. To analyze the relative importance of hydraulic and biological controls on biofilm N uptake, we measured turbulence, biofilm N uptake using a stable isotope t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Flow pathways from different sub‐ecosystem compartments converge along the river network. The varying residence times, contacting volumes, and stream substrates also create spatial and temporal variations in biogeochemical reactions (Anlanger et al., 2021; Harvey et al., 2019). Net NO 3 − ‐N uptake (UNET ${U}_{NET}$) during the 2019‐05 WE_2 campaign was among the highest, potential because this was a more natural stream reach and occurred right after the annual wet season (Figure 1; Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Flow pathways from different sub‐ecosystem compartments converge along the river network. The varying residence times, contacting volumes, and stream substrates also create spatial and temporal variations in biogeochemical reactions (Anlanger et al., 2021; Harvey et al., 2019). Net NO 3 − ‐N uptake (UNET ${U}_{NET}$) during the 2019‐05 WE_2 campaign was among the highest, potential because this was a more natural stream reach and occurred right after the annual wet season (Figure 1; Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Its compact and modular design also allows the MOBICOS infrastructure to easily be transferred between sites or operated at multiple sites simultaneously. Between‐site replication of the same experimental design under different initial environmental conditions improved the understanding of causal relationships between natural environmental oscillations of aquatic ecological states and water quality (Anlanger et al., 2021; Graeber et al., 2021), anthropogenic stressors (Sunjidmaa et al., 2022), and their combined ecological impacts on these aquatic ecosystems (Iannino et al., 2021; Weitere et al., 2021).…”
Section: Tereno—a Network Of Four Integrated Environmental Observatoriesmentioning
confidence: 99%
“…Previous research has demonstrated that elevated near-bed turbulence enhances the downward transport of dispersal cells through the water column to the benthic compartment (Besemer et al 2009) and increases nutrient uxes (Anlanger et al 2021;Risse-Buhl et al 2017). Thus, we suggest that the low turbulence above the ne sediment substrate might be the underlying cause for the observed lower NO3 uptake in the benthic compartment of the ne sediment treatment compared to the control.…”
Section: Contrasting Effects Of Ne Sediment In the Benthic And Hyporh...mentioning
confidence: 99%